Management of neovascular age-related macular degeneration: Taiwan expert consensus - Ling Yeung (Elsevier, 2021)
Neovascular age-related macular degeneration (nAMD) is a leading cause of irreversible vision loss. The present consensus provides suggestions on diagnosis, evaluation, treatment, and follow-up strategies for nAMD from a panel of 11 practicing ophthalmologists. The experts suggest that the baseline visit for nAMD management should include a comprehensive ophthalmologic examination via a multimodal approach consisting of visual and anatomical evaluation. Patients diagnosed with nAMD should be subjected to treatment with the goal of maintaining visual function while diminishing anatomical disease activity and minimizing treatment burden. Currently, anti-VEGF therapy is the main treatment strategy for nAMD, and evaluation involving comprehensive ophthalmologic examination within 1 month of completion of the loading phase comprising three monthly injections is recommended to guide subsequent management. Either a treat-and-extend or pro re nata regimen can be considered for the maintenance phase of anti-VEGF therapy, and the regimen should be chosen and adjusted according to disease activity, reimbursement criteria, financial burden, and patient preferences. In the event of inactive nAMD or poor treatment outcomes, after thorough evaluation and patient education, anti-VEGF therapy may be stopped. The consensus provides practical nAMD management guidelines for ophthalmologists and fellow healthcare professionals.